Climate change induced the altering in precipitation characteristics across the rice cultivation paddies of Vietnam - Nguyen, Q. C.; Ngo, H. Y. T.; VU, M. H. T. (MAUSAM, 2024)
Globally, it has enough convincing evidence to assert that climate variability is the main factor causing the change in precipitation characteristics (CPCs). Appraising the CPCs are, therefore, crucial for local agricultural activities. The aim of this study is to investigate the CPCs across the rice cultivation paddies (RCPs) of the Long Xuyen Quadrangle (LXQ) in Vietnam as a typical case of the impacts of climate change (ICC) on the agricultural sector. To achieve the intended objective, firstly daily precipitation data series at 9 observation stations across the LXQ throughout 1978-2021 were appraised for quality by applying the homogeneity tests. Secondly, appraised precipitation data were investigated the CPCs applying a set of non-parametric approaches, and finally, the spatial distribution maps of the CPCs across the study area were shown off based on the Thiessen polygon algorithm integrated into the ArcGIS (Version 10.8) software. With a 95% confidence level, the findings revealed that a statistically insignificant downward trend for annual precipitation and wet seasonal precipitation was recorded along the coastal arable land edges while the statistically insignificant upward trend was detected along the RCPs in the northeast to southeast part. One striking feature the study results revealed is that a statistically insignificant uptrend (ZMK = 0.043 ~ 0.126) was observed for precipitation in the dry season. The findings could contribute positively to agricultural activities during the summer-autumn crop season.